Analysis Digital Customer Satisfaction in Online Purchase - Rezeki, Sry; Muliauwan, Shelly Christiana (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2021)
In this digital era, everything has switched to an online system, starting from shopping, vehicles, ordering food, everything can be done online, everything can be obtained easily, just install an application to support online activities, we can meet all our needs, with the sophistication of technology, of course it makes it easier for us at all times. We can take activities for example when we buy clothes online, it certainly makes it easier for us from going to the market or mall to get clothes, now we just have to sit at home, open the application and clothes or orders will arrive directly at the door This study was conducted to test the level of customer satisfaction in making online purchases where the researchers made direct observations by monitoring the ratings given by customers on the online shopping site that is widely used by the public, namely Shoppe. The research method used is a qualitative descriptive method in which data is obtained directly through interviews with shopee users and observing assessments given by customers in the shopee application. The results obtained from this study are that many people feel satisfied after shopping online because they consider online shopping can save time, effort and get cheaper prices than traditional markets.